(untitled) (Research, Society and Development, 2020)
The objective of this research was to obtain composites using petioles bamboo and ophthalmic lens waste powders and polyester resin. Such materials have no defined application, they are produced in large quantities and their waste is discarded irregularly in landfills. Bamboo and ophthalmic lens rejects powders were produced, with particle sizes of 2.07 mm and 1.14 mm, respectively. Preliminary tests were carried out to determine the maximum quantities of each material to be mixed with the polyester resin matrix, in order to guarantee the good processability of the new material produced. The mass quantities used were 10 and 15% bamboo, 15 and 40% tailings and a hybrid composition with 5% bamboo and 20% tailings, to obtain the desired composites. The composite plates were manufactured by the cold compression wet molding process in closed mold. Several tests were carried out to characterize the composites that were produced. It was found a decrease in the mechanical strength of the composite in comparison to the matrix, concluding that the bamboo powders and ophthalmic lens waste had a filling load function in the composites produced. The most expressive result of the composites was in the impact resistance, corresponding to 0.55 J/cm2 for OLWP 40% higher in 39.6% in relation to the polyester resin matrix. As a practical application, table and bench tops were manufactured with the most economically and ecologically viable composite, 40% OLWP.